Research progress on prevention of recurrence of venous leg ulcer (下肢静脉溃疡再复发预防的国内外应用研究进展) - FANG Meng (方孟); JIANG Huijiao (蒋慧娇); YANG Wenjuan (杨文娟); DAI Min (戴敏) (中西医结合护理, 2021)
Venous leg ulcers (VLU) associated with chronic venous insufficiency have a high rate of recurrence, reinforcing the chronic ulcer and causing a potentially vicious cycle. In this paper, the risk factors and nursing care of VLU relapse were reviewed. Based on evaluation of risk of recurrence, targeted measures were carried out to reduce the risk factors of recurrence in primary prevention, to prevent venous disease from causing VLU recurrence in secondary prevention, and to taking various means of treatment to actively treat patients with existing VLU. (下肢静脉溃疡(VLU)治愈后复发率及复发次数高, 甚至形成溃疡-愈合-复发的恶性循环, 且可能伴随终身。本文通过对VLU再复发各个阶段的危险因素及预防措施进行综述, 包括: 一级预防针对再复发高危因素采取相应措施; 二级预防主要防止静脉疾病造成VLU复发; 三级预防采用各种手段治疗积极治疗患者现有VLU, 杜绝其再复发。)